IMPROVING WRITING DESCRIPTIVE TEXT BY USING NLP STRATEGY AT VIII GRADE OF SMPN 11 DURI - Dahler Dahler (Lectura : Jurnal Pendidikan, 2016)
This research is based on the problem faced by the students such as: difficulty inunderstanding the generic structures of descriptive text and the difficulties in developingparagraph. The purpose of this research was to improve the students’ writing skill by usingNeuro Linguistics Programming (NLP) strategy at VIII grade of SMPN 11 Mandau Duri. Theresearch design was Classroom Action Research (CAR) consisted of two cycles. The datawere collected by using test, field note, observation sheet, and interview. Then, the datacollected were analyzed by using scoring rubric of writing descriptive text. The result showedthat students’ ability in writing descriptive text could be improved. It could be seen frombased score of students writing skill was 38 (failed) improve to 51 (failed) in cycle 1 to 70(Pass) in cycle II. It was caused by some factors, those were the teacher gave motivation,created enjoyfull experience, comfortable class and used various media. In conclusion, theuse of NLP strategy has many beneficial.